GROUNDWATER CHEMISTRY OF THE PLIO-PLEISTOCENE AQUIFER OF ERBIL HYDROGEOLOGIC BASIN, N.IRAQ. - AL-Kubaisi, Qusai (Iraqi Journal of Science, 2024)
The studied aquifer is the Plio-Pleistocene unit of layering mixed facies of gravel, sand, silt and clay with respect to conglomerate. Two hydrochemical groups were identified as bicarbonate and sulphate. Two families in each group are strongly acting with depth and laterally a part from the hydrogeologic boundaries.The bicarbonate families are Ca-HCO3and Mg-HCO, while that of sulphate are Mg-SOand Na-SO. The distribution map of salinity reflects a trend of increase in salinity which clarify the different flow orientation within the sub-basins. The minimum recorded of salinity is 750 ppm, while the maximum is 7500ppm. The ten folds salinity occurs at the western boundary condition of Avana and Khurmala anticlines, where the Fatha gypsum layers exposed. This condition of salinity coincide’s with sulphate distribution below 1 epm toward north –north east and above 1 epm up to 10 epm toward NW, and west. The chloride ionic concentration( isochloride map) shows a restricted area of more than 1 epm up to 10 epm east Khurmale anticline of sulphate. 344Water quality of this aquifer system with SAR values less then unity group and more than unity. Most of these waters are marginal good quality for irrigation .The deep groundwater and highly infiltration rate leads to practices of saline water irrigation of sprinkler type.